2013
DOI: 10.1371/journal.pone.0075053
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Sandalwood Oil: Santalum album CYP76F Cytochromes P450 Produce Santalols and Bergamotol

Abstract: Sandalwood oil is one of the world’s most highly prized essential oils, appearing in many high-end perfumes and fragrances. Extracted from the mature heartwood of several Santalum species, sandalwood oil is comprised mainly of sesquiterpene olefins and alcohols. Four sesquiterpenols, α-, β-, and epi-β-santalol and α-exo-bergamotol, make up approximately 90% of the oil of Santalum album. These compounds are the hydroxylated analogues of α-, β-, and epi-β-santalene and α-exo-bergamotene. By mining a transcriptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 33 publications
2
93
0
2
Order By: Relevance
“…In most cases, however, CYP76s seem to be involved in terpenoid metabolism. CYP76Ms from monocots were found to metabolize diterpenoids for the synthesis of antifungal phytocassanes (Swaminathan et al, 2009;Wang et al, 2012;Wu et al, 2013), CYP76AH1 from Salvia miltiorhizza and its ortholog CYP76AH4 from rosemary (Rosmarinus officinalis) were shown to hydroxylate the norditerpene abietatriene in the pathway to labdane-related compounds (Zi and Peters, 2013), whereas CYP76Fs from sandalwood (Santalum album) were found to hydroxylate the sesquiterpenes santalene and bergamotene (Diaz-Chavez et al, 2013). CYP76B1 from Helianthus tuberosus was, however, found to metabolize herbicides belonging to the class of phenylurea (Robineau et al, 1998;Didierjean et al, 2002), but its physiological function was not reported.…”
mentioning
confidence: 99%
“…In most cases, however, CYP76s seem to be involved in terpenoid metabolism. CYP76Ms from monocots were found to metabolize diterpenoids for the synthesis of antifungal phytocassanes (Swaminathan et al, 2009;Wang et al, 2012;Wu et al, 2013), CYP76AH1 from Salvia miltiorhizza and its ortholog CYP76AH4 from rosemary (Rosmarinus officinalis) were shown to hydroxylate the norditerpene abietatriene in the pathway to labdane-related compounds (Zi and Peters, 2013), whereas CYP76Fs from sandalwood (Santalum album) were found to hydroxylate the sesquiterpenes santalene and bergamotene (Diaz-Chavez et al, 2013). CYP76B1 from Helianthus tuberosus was, however, found to metabolize herbicides belonging to the class of phenylurea (Robineau et al, 1998;Didierjean et al, 2002), but its physiological function was not reported.…”
mentioning
confidence: 99%
“…General terpenoid metabolism genes which are early in the pathway, 3-hydroxy-3-methylglutaryCoA reductase (hmgr: Supplement S1), 1-deoxyxylulose-5-phosphate synthase (dxs1: Supplement S1) and isopentyl diphosphate isomerase (ippi2: Supplement S1), were used in the analysis (Cane 1990;Külheim et al 2011) as well as genes known to be involved in sandalwood specialized sesquiterpenol biosynthesis (farnesyl diphosphate synthase (SaFPPS-HQ343293), santalene synthase (SaSSy-HQ343276), bisabolene synthase (SaBS-HQ343279), sesquiterpene synthase (SaSTPS-ACF24768), sesquisabinene synthase (SaSQBS-HQ384285)) (Jones et al 2011, Moniodis et al 2014. The cytochrome P450 gene, SaCYP76F38v2 (KC533718), which is a member of the sandalwood CYP76F group of sesquiterpenol biosynthesis (Diaz-Chavez et al 2013;Moniodis et al 2014) was also included. Two homologues of cytochrome P450 genes involved in terpenoid oxidation from subfamilies 72 and 716B in other plants (SaCYP72 and SaCYP716B: Supplement S1) were selected (Fukushima et al 2011;Vetter et al 1992) as they also had unusually high transcript abundance in oil producing ray parenchyma of S. album.…”
mentioning
confidence: 99%
“…It will provide a foundation for production of sandalwood oil for the fragrance industry by means of metabolic engineering, as demonstrated with proof of concept formation of santalols and bergamotol in engineered yeast cells, simultaneously addressing conservation challenges by reducing pressure on supply of sandalwood from native forests. [31] www.wjpps.com …”
Section: Effect Of Sandalwood Oil and Treatment Of Mental Disordersmentioning
confidence: 99%